Psychologically accessing ownership : how does Individual Psychological Ownership (Ipo) affect Peer-To-Peer Access-Based Consumption (P2p-Abc)? - Teixeira, Otávio Ferreira Borges (2021)
Tese (doutorado) — Universidade de Brasília, Faculdade de Economia, Administração e Contabilidade e Gestão Pública, Programa de Pós-Graduação em Administração, 2021.